Delays and errors in abnormal chest radiograph follow‐up: a systems approach to promoting patient safety in radiology. Issue 4 (20th May 2014) - Bhaludin, Basrull Najmi; Shelmerdine, Susan Cheng; Arora, Sonal; Senbanjo, Taiwo; Parthipun, Arum
Abstract Rationale, aims and objectives This study aimed to apply the 'systems approach' to patient safety in order to identify causes for delays and errors in lung cancer diagnoses following an abnormal chest radiograph. Methods In the first part of this study, the systems approach to patient safety was comprehensively reviewed by three radiologists and seven patient safety experts. In the second part of this study, a retrospective review was performed of all patients referred to the lung cancer multidisciplinary team (MDT) meeting over a 1‐year period. All abnormal chest radiograph reports were examined and a root–cause analysis performed of cases where errors and delays in diagnoses were deemed to have occurred. Results A total of 124 cases were reviewed, of which 36 (29%) patients had an abnormal preceding chest radiograph prior to MDT referral. In six cases, serious errors from delay and lack of follow‐up were identified. These are analysed and discussed in detail in this article. Application of the systems approach to each case identified poor communication and lack of clinical action as prime causes. Conclusions Both reporting radiologists and referring clinicians have a responsibility to ensure appropriate action following an abnormal chest radiograph. The main error lies in communication between the referring clinicians and the radiologists. Direct electronic communication is potentially a more robust method to overcome this.